Factors affecting the early failure of implants placed in a dental practice with a specialization in implantology - a retrospective study - Krisam, Johannes; Seyidaliyeva, Aida; Rammelsberg, Peter; Zenthöfer, Andreas (BMC oral health, 2019)
Background: To evaluate early failure and possible risk factors for failure of dental implants placed under practice-based conditions. Methods: To clarify the research question, anonymized data from 106 patients with 186 dental implants were analyzed. The presence of sucessful healing (yes/no) at the time of incorporation of the final prosthesis was assessed. Mixed models were compiled for each target variable to enable estimation of the effects of patient-related and implant-related conditions on the risk of early implant failure. Results: Nine out of 186 implants (4.8%) placed in 106 participants failed before incorporation of the final prosthesis. The use of shorter implants (< 10 mm) and the need for augmentation procedures were associated with a greater risk of early implant failure. For shorter implants, the risk was 5.8 times greater than that for longer implants (p = 0.0230). Use of augmentation procedures increased the risk by a factor of 5.5 (p = 0.0174). Conclusions: Implants placed in the dental practice with a specialization in implantology heal successfully. The use of augmentation procedures and of implants shorter than 10 mm seems to be associated with a greater risk of early implant failure.
Gesehen am 08.10.2019